Bimetallic MOF-derived composites with broad electromagnetic wave absorption and strong corrosion resistance. (May 2023) - Xie, Tianwen; Li, Shuaizhen; Ma, Lin; Li, Jian; Pang, Shengyang; Hu, Chenglong; Zhao, Rida; Tang, Sufang
Abstract: With widespread requirements of electromagnetic wave absorption in 5G era, the advanced wave-absorbing materials with corrosion resistance are urgently required. Herein we have synthesized a bimetallic NiZn-MOF-derived composite with broad electromagnetic wave absorption and strong excellent corrosion resistance using a facile hydrothermal method. Based on the composition modulation of the produced Ni/Ni3 ZnC0.7 particles, dense and continuous carbon shell can be formed and eventually encapsulate the particles. The resulting composite has an optimum reflection loss of −56.8 dB at 2.40 mm and an effective absorption bandwidth of 5.9 GHz at 2.34 mm. Besides, it remains stable after 6-month immersion in the corrosive mediums, suggesting its long-term corrosion resistance. This work provides a way to prepare MOF-derived wave absorbing materials with anti-corrosion function. Graphical abstract: Image 1 Highlights: Facile synthesis of bimetallic NiZn-MOF-derived electromagnetic wave absorbing material through hydrothermal method. The resulting material has an optimum reflection loss of −56.8 dB and an effective absorption bandwidth of 5.9 GHz. The material also exhibits significant long-term corrosion resistance in corrosive mediums.